(untitled) (Applied Biological Research, 2023)
The focus of this study was to investigate the acute toxicity, growth and survival esponses of earthworm species Eudrilus eugeniae, exposed to textile dye effluent. The textile dye effluent samples were collected from Erode, Tamil Nadu (India) and analysed for physicochemical parameters and heavy metal content. The effluent samples were used in subsequent toxicity and biochemical tests on eugeniae. Garden soil was used incomprehensive study on the behaviour of eugeniae. The natural soil test method was used to expose the epigeic earth worm species E. eugeniae to varying concentrations (5 to 25 mL kg-1) of textile effluent for 7 and 14 days. The results revealed that the LC50 values of textile effluent were 26.55 and 6.586 mL kg-1 after 7 and 14 days, respectively. The lethal effects oftextile effluentwere assessedby exposingearthwormsto5 concentrations 5, 10, 15, 20, and 25 mL kg-1) of LC50 of textile effluent for 28 days to record fecundity and growth rates. Maximum growth of earthworms was observed in control group (10.12 cm length and 6.04 g weight) while effluent-treated earthworms showed reduced growth with increased effluent concentration affecting the growth more severely. A lower number of cocoons and young ones (31.4 cocoons and 107.4 young ones) were observed in high concentration (25 mL kg-1) of textile effluent in comparison to the control group (65.6 cocoons and 306.4 young ones). The study revealed that textile effluents cause potential health risk to E. eugeniae if exposed to high concentrations.